Effects of a holistic, patient-centered approach on breast cancer relative dose intensity. Issue 2 (May 2019) - Louison, Rebecca; Lee, Jennifer; Roe, Victoria; Ghosh, Chirantan
Highlights: Patient records from a community oncology clinic were retrospectively evaluated and de-identified before coding and analysis. (p.3). Participants were 161 consecutive BC patients from 1/15/1998 to 7/18/2013. Inclusion criteria included referral for adjuvant chemotherapy. Exclusion criteria included non-curative and/or palliative patients. (p.3). Take Home message. Average Relative Dose Intensity at patient- centered holistic clinic was 0.96 (p.6). Higher Relative Dose Intensity was associated with ER + and HER2 status (p.7). Relative Dose Intensity had a statistically significant positive association with BMI (p.7). Of patients had a Relative Dose Intensity above the recommended 092% of patients had an RDI above the recommended 85%(p.6). Abstract: Purpose: A critical component of breast cancer (BC) chemotherapy effectiveness is relative dose intensity (RDI), as <85% RDI lessens treatment efficacy. Over half of BC patients have an RDI < 85% due to dose-limiting treatment side effects. Evidence suggests nonpharmacologic approaches (e.g., yoga, nutrition) improve cancer symptoms (e.g., pain, fatigue), yet no studies examined them for RDI. This descriptive, preliminary study will investigate the effects of a patient-centered, holistic approach on RDI, and associations among RDI and patient characteristics (age, race, ethnicity, body mass index, body surface area, hormone status [estrogen- or progesterone-receptor positive, HER2, menopause], marital status, employment status, cancer stage, treatment type, insurance type). Methods: The medical records of 161 BC patients ( M = 61.5 years, SD = 12.7) from a holistic cancer clinic were collected and analyzed. This clinic offers a patient-centered approach (i.e., patients actively make decisions, treatment education, chair yoga, reiki, and nutritional counseling). RDI was determined by calculating the ratio of the received dose versus the intended dose intensity. Results: 92% of patients had an RDI ≥ 85% (Mean = 96%) and 8 of the 9 treatment regimens' RDI exceeded 85%. RDI had a significant positive association with BMI ( p = .06), and being ER+ and/or HER2+ ( p's  = .08). None of the remaining demographic or clinical characteristics were associated. Conclusions: This non-pharmacologic approach led to a higher RDI than recommended, potentially improving BC patients' prognosis. Higher RDI was related to BMI, and ER+ and HER2 status. Additional research is needed; however, these results provide promising evidence regarding the benefits of a patient-centered, holistic approach.